ANALYSIS, QUANTIFICATION AND IDENTIFICATION OF WORM EGGS UNDER A MICROSCOPE - Bahramov Rustam Rakhmatullaevich; Egamberdiev Sukhrobjon Hasan o’g’li (Journals Park Publishing, 2024)
Millions of people throughout the world suffer from parasite infections. Traditionally, technicians use manual eye inspection of microscopic specimens to perform a parasite examination. However, manual operations have limitations that hinder the ability to obtain precise egg counts and cause inefficient identification of infected parasites on co-infections. The technician requirements for handling a large number of microscopic examinations in countries that have limited medical resources are substantial. We developed the helminth egg analysis platform (HEAP) as a user-friendly microscopic helminth eggs identification and quantification platform to assist medical technicians during parasite infection examination.
Keywords: Helminth; Parasite egg examination; Deep learning; Object detection; Web server; Database.